Socialization And Training With Verticulture Agricultural Methods in Jetis Dau District Of Malang Regency During The Covid-19 Pandemic - Sutriaman Sutriaman; Mohammad Zulizar (Archipelago, 2021)
The purpose of this service program is to socialize verticulture agriculture to the jetis community during the covid-19 pandemic so that they can grow crops in home yards that have relatively small land. In the simple model, the basic structure used is easy to follow and the materials are easy to find, so it can be applied in homes. Additional systems that require special skills and knowledge, for example the use of hydroponic systems or drip irrigation.